Enhancing Quality of Life and Reducing Anxiety in Children with Leukemia Through Social Support: A Pilot Cross-sectional Study - Kutahyalioglu, Nesibe S.; Demirbas, Gamze (Indian Journal of Medical and Paediatric Oncology, 2025)
Approximately 400,000 new cases of cancer are diagnosed annually among children and adolescents. Leukemia, the most prevalent pediatric cancer, is a leading cause of mortality in children under 15 years of age. Despite advances in treatment, patients often face remarkable social and academic challenges. The literature underscores the necessity of developing strategies to address these difficulties and provide comprehensive support to children with leukemia.This pilot cross-sectional study aimed to enhance emotional well-being and resilience in children with leukemia by fostering a sense of solidarity and self-efficacy through interactions with mentors who have successfully recovered from leukemia.The intervention involved 12 participants (7 girls and 5 boys, mean age = 10 years) from the country's eastern provinces. Over 3 months, these children engaged in online sessions with recovered leukemia survivors who provided motivational and academic support.The findings revealed statistically significant improvements in participants' trait anxiety (p = 0.029), general quality of life (p = 0.007), and coping skills related to cancer (p = 0.005). These results indicate that the mentorship program positively influenced the psychological and social well-being of children with leukemia.This initiative demonstrates the potential of such programs to mitigate motivational challenges, foster social benefits, and contribute to pediatric cancer patients' long-term health and productivity.
Keywords: children; leukemia; mentorship; quality of life; anxiety; coping skills